Commando [videorecording (DVD)] - Loeb, Jeph; De Souza, Steve; Weisman, Matthew; Schwarzenegger, Arnold; Hedaya, Dan; Milano, Alyssa; Chong, Rae Dawn; Kelly, David Patrick; Wells, Vernon, 1945-; Olson, James, 1930-2022 (20th Century Fox Home Entertainment, 2011)
Martial arts expert and retired commando, Colonel John Matrix, travels to South America to find his daughter after she is kidnapped by a vicious dictator.